Pengaruh Lingkungan Kerja, K3 dan Stres Kerja Terhadap Kinerja Karyawan Studi Kasus Pada Perusahaan UD. FARHAN JAYA Depok, Jawa Barat - Fernandha, Zanuar Farhan; Khalikussabir, Khalikussabir; Amin, Muhammad Sirojuddin (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study aims to analyze the influence of the work environment, occupational health and safety (K3), and work stress on employee performance at UD. Farhan Jaya, Depok. The background of this research is based on the importance of creating a conducive and low-pressure work environment to support productivity. This study uses a quantitative approach with a survey method through the distribution of questionnaires to 51 employees of the production department. Data analysis was carried out by validity, reliability, multiple linear regression, t-test, F test, and determination coefficient. The results showed that the work environment and work stress had a positive and significant influence on employee performance, while K3 had no significant effect. Simultaneously, the three independent variables had a significant effect on employee performance with a contribution of 25.1%. These findings indicate that the creation of a harmonious work environment and good stress management can optimally improve employee performance, while the implementation of K3 needs to be reviewed to be more impactful. This research contributes to the development of HR management strategies based on environmental and work psychological factors. Keywords: Work Environment, K3, Work Stress, Employee Performance